Mengembangkan Kemampuan Berpikir Kritis dalam Pembelajaran Kelas Rangkap - Anggun Putri Pradani; Florentic Helaub; Memorila Dini Oktavia; Miftaudin Mahfudz; Putri Alya; Rizka Selviana Putri (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines strategies for developing students’ critical thinking skills in multigrade classrooms through a literature review method. Findings reveal that effective multigrade teaching hinges on creative approaches—including Problem Based Learning (PBL), cross-grade collaboration, visual media utilization, task differentiation, higher-order thinking (HOT) questions, and critical reflection—with the teacher’s facilitative role being pivotal in fostering an inclusive learning environment. Key challenges such as age diversity, varied academic abilities, and resource constraints are addressable through teacher training and adaptive instructional design. The study culminates in practical guidelines for teachers to efficiently manage multigrade settings while nurturing critical thinking skills centered on analysis, evaluation, and decision-making.